PENGARUH GAYA HIDUP DAN KEMUDAHAN BERBELANJA ONLINE TERHADAP MINAT BELI MAHASISWA PENDIDIKAN EKONOMI 2019 STKIP PGRI BANGKALAN - Riska Amelia; Ruski Ruski; Subandy Widjaya (POLITEKNIK LP3I JAKARTA, 2023)
The basis of this research is the ease of shopping online, with online trading sites, so that people do not need to come to shopping centers and can buy the goods they need just by looking at the pictures and specifications of the goods. This research was made to find out the Effect of Lifestyle and Ease of Shopping Online on the Buying Interests of Economics Students 2019 STKIP PGRI BANGKALAN. A quantitative research approach was adopted for this study. The sample consisted of 30 respondents. using a basic random sample approach with sample probability. The questionnaire is used as a research instrument measurement tool. Multiple Linear Regression Test, Hypothesis Test, and Classical Assumption Test are used in statistical analysis. Based on research findings, lifestyle (X1) and ease of online shopping (X2) have a partial influence on the purchase intention of 2019 STKIP PGRI Bangkalan Economic Education Students (Y). Lifestyle (X1) and Ease of Online Shopping (X2) have quite a big influence on STKIP PGRI Bangkalan Economic Education Students' Purchase Interest (Y). The calculated R Square value of 0.788 indicates that the combined effect of variables X1 and X2 on variable Y is 78.8%, with the influence of other factors not included in this study taking into account the remaining effect.Key words: Lifestyle, Ease of Online Shopping, Buying Interest